Pengaruh Penerbitan Sukuk Ijarah Dan Ukuran Perusahaan Terhadap Profitabilitas ( Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020) - Ade, Ade Irma Suryani; Sucipto Sucipto; Eri Nofriza (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study was to determine the effect of the issuance of sukuk ijarah and company size on the profitability of companies listed on the Indonesia Stock Exchange in 2017-2020. This research is quantitative descriptive. The data used is secondary data obtained from the annual reports of companies incorporated in the Indonesia Stock Exchange in 2017-2020. The research sample was obtained from the purposive sampling technique, namely 8 companies with 4 years so that there were 32 observations. The data analysis technique used Multiple Regression Analysis. Partially, the issuance of sukuk ijarah and company size affect the profitability of companies listed on the Indonesia Stock Exchange in 2017-2020. Simultaneously, the issuance of sukuk ijarah and company size together affect the profitability of companies listed on the Indonesia Stock Exchange in 2017-2020. Based on the results of the coefficient of determination, the magnitude of the effect of the issuance of sukuk ijarah and company size on overall profitability is 0.227 = 22.7% and the rest is influenced by other variables not included in the study.